2018
DOI: 10.1007/s10856-018-6090-0
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Osteogenic prospective of deriving human dental stem cells in collagen matrix boost

Abstract: The original version of this article unfortunately contained a mistake. The country was incorrect in the authors affiliations. It should read as "ROC". The corrected affiliations are given below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…They reported that the use of BFP-derived cells in addition to natural bovine bone mineral may be a satisfactory approach for bone regeneration in these cases. However, a study from Fang et al (2017) 32 reported that the dental pulp stem cells presented a higher osteogenic potential when compared with the BFP stem cells and the periodontal ligaments stem cells. The present literature review identified the anatomy of the BFP, including its development, functional importance and some of its applications in different clinical procedures.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…They reported that the use of BFP-derived cells in addition to natural bovine bone mineral may be a satisfactory approach for bone regeneration in these cases. However, a study from Fang et al (2017) 32 reported that the dental pulp stem cells presented a higher osteogenic potential when compared with the BFP stem cells and the periodontal ligaments stem cells. The present literature review identified the anatomy of the BFP, including its development, functional importance and some of its applications in different clinical procedures.…”
Section: Discussionmentioning
confidence: 97%
“…The study of the BFP is important to know about the possible applications and risks in clinical practice, minimal morbidity procedures 31 . Cells from the BFP have been considered an ideal source for bone tissue engineering 26,32 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations